Pengaruh Literasi Keuangan terhadap Kinerja Usaha UMKM di Desa Palem Watu, Kecamatan Menganti, Kabupaten Gresik - Fasya Raihan Anwar, Redhinta; Vira Angelina (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to analyze the effect of financial literacy on MSME business performance in Palem Watu Village, Menganti Sub-district, Gresik Regency. Financial literacy, which includes understanding and ability to manage finances, is expected to contribute positively to the business performance of MSME actors. The research method used is a quantitative approach using a simple linear regression test analysis method. The data obtained are MSMEs in Palem Watu Village. The results of this study indicate that financial literacy has a significant effect on the performance of MSMEs. The results of the coefficient of determination analysis show an r square value of 65.2%, while the remaining 13.7% is influenced or caused by other factors not included in the study.